No-Code Technology in Designing a Web-Based Stock Recording Applications Using AppSheet - Herawati, Amanda Putri; Budiman , Thomas; Sianipar , Anton Zulkarnain; Lumbantobing, Balthasar Sebastian (Jurnal Teknologi Informatika dan Komputer, 2025)
The development of information and communication technology in the digital era has brought significant changes to various sectors, including trade and distribution. The use of technology allows businesses to improve operational efficiency, accelerate workflows, and support more accurate decision-making. Digital transformation also helps minimize errors and maintain service quality. Manual inventory recording at the Dermaga Baut Mandiri Store in Tangerang causes difficulties in monitoring inventory availability, a high risk of data errors, and delays in reporting, which impacts operational and service continuity. This study aims to design and implement a web-based inventory recording application using AppSheet as a no-code solution to improve accuracy, efficiency, and ease of inventory management. The method used is a prototype method with stages of communication, rapid planning, initial design, prototype creation, and testing and feedback. Data were collected through observations and interviews with store owners and staff, then analyzed descriptively and qualitatively. The results show that the developed application is able to accelerate the recording process, display minimum stock notifications, and generate real-time stock reports that are easy to print in PDF format. Users found the app easy to use, helpful in inventory monitoring, and faster decision-making. The app, designed using no-code technology for operational digitization, is expected to improve competitiveness and customer service quality.